MULTIPARADIGMA DALAM ETIKA DAN AKHLAK KEPERILAKUAN DIBIDANG ILMU AKUNTANSI - Harfiahani Indah Rakhma Ningtyas (Jurnal Transparan Institut Teknologi dan Bisnis Yadika, 2021)
Accounting is a system that produces financial information that is used by its users for making a decision. The purpose of the information is to provide guidance in choosing the best course of action in allocating scarce resources in economic business activities. Thus, accounting cannot be separated from human behavior that requires information. To carry out daily activities or the surrounding environment. So that accounting is not something passive, but accounting will always evolve throughout its era. In this study will discuss about a debate between academics and practitioners "whether there is a relationship between behavioral accounting and accounting science in a multiparadigm point of view (Interpretivism). This study aims to determine how important behavioral accounting is in the field of accounting science (financial accounting, cost accounting). and management, and public sector accounting. This study uses an interpretive qualitative paradigm. This study attempts to explain the relationship between action and meaning. The research subjects are several lecturers in Indonesia who represent various fields of accounting. an accountant and manager in terms of financial accounting, cost and management, and finally public sector accounting. It is very clear that a manager and accountant is obliged to perform an ethical action must be in accordance with the standards or rules that have been set.